Australia and Latin America : Challenges and Opportunities in the New Millennium - Barry Carr; John Minns (ANU Press, 2014)
This is a good time to reflect on opportunities and challenges for Australia in Latin America. Impressive economic growth and opportunities for trade and investment have made Latin America a dynamic area for Australia and the Asia Pacific region. A growing Latin American population, Australia's attractiveness to Latin American students, a fascination with the cultural vibrancy of the Americas and an awareness of Latin America's increasingly independent stance in politics and economic diplomacy, have all contributed to raising the region's profile. This collection of essays provides the first substantial introduction to Australia's evolving engagement with Latin America, identifying current trends and opportunities, and making suggestions about how relationships in trade, investment, foreign aid, education, culture and the media could be strengthened.